How Can the Protection of Important Agricultural Heritage Sites Contribute to the Green Development of Agriculture: Evidence from China - Li Mo; Song Chen; Shenwei Wan; Lei Zhou; Shiyuan Wang (Agriculture)
The protection of agricultural heritage sites has become a global human responsibility and consensus. However, the potential effect of agricultural heritage sites on the green development of agriculture has currently been ignored. Since ancient times, China has been founded on agriculture, and the number of important agricultural cultural heritages ranks first in the world, with strong representativeness. The two-way fixed effects model was employed to empirically test the positive impact of agricultural heritage site protection on the green development of agriculture, utilising data from 30 provincial units in China over a 21-year period from 2001 to 2021 in this paper. Additionally, a mediating effect model was used to test the potential mechanism. The specific conclusions are as follows: firstly, the protection of agricultural heritage sites has a significant positive effect on the green development of agriculture; secondly, the protection of agricultural heritage sites can advance the agricultural industrial structure, increase the land transfer rate, strengthen the construction of new agricultural management organisations, enhance financial investment in supporting, and promote green technology innovation. The five paths were found to have passed the mediation effect test. Thirdly, the positive effect of protecting agricultural heritage sites on the green development of agriculture is heterogeneous. Specifically, the effect is more pronounced in the eastern and central regions, particularly in areas with higher levels of AI development and lower urbanisation. The ultimate objective is to utilise evidence from China to develop nature-based solutions for the protection and utilisation of agricultural heritage and green development of agriculture in other world agricultural heritage sites.